PROYECTO DE FACTIBILIDAD PARA LA CREACIÓN DE UN RESTAURANT DE PARRILLADAS EN EL SECTOR CÉNTRICO DEL CANTON CELICA DE LA PROVINCIA DE LOJA - González Cartuchi, Karen Tatiana (2016)
For decades, the province of Loja and particularly the Canton Celica, is affected by a small business development, being a limitation on their progress, as has become a canton consumer with an almost imperceptible growth of productive activities. Most companies producing and marketing of goods and / or services on our canton are implemented empirically set that are not considered essential technical aspects to achieve the desired success, thus failing to provide adequate profit margins that allow their growth, development and permanence in time. This fact constitutes a challenge for the new generation of professionals who must find viable and profitable alternative, where skilled labor take advantage, access to new technology and especially to identify market needs to satisfy . This is why it intends to conduct a "feasibility project for the creation of a restaurant-grill in the downtown area of Canton Celica in the province of Loja" For this work he was based methods and techniques that helped identify the population which are: deductive, inductive method that allowed synthesize the information obtained, as well as the techniques used which are: the survey interview, direct observation and sampling, the same who helped collect basic information about the product and be able to know the level of feasibility for the creation of the company. The results determined in this study are: Market research determines that the potential of the project in 2014 demand of 1703 households, the actual demand is 1703 and 1465 effective demand is the 6 same as multiplying by 19 which is the average consumer and obtain effective demand percapita of grilled 27834; the offer is 14280 barbecues, while demand is unmet 13554 barbecues. The technical study is determined that the installed capacity of the project is 12000 barbecues and capacity utilization is 7680 annual barbecues. Organizational design in the trade name of the company was established as a limited liability company. "GRILLED THE CELESTIAL" Cia. Ltda. In the financial study it determines the company for initiation requires an investment of $ 14.190,00 US dollars. Among the sources of funding there is a credit to the Development Bank which amount represents 30% of the investment; costs for the first year are $ 52.991,00 US dollars, revenue of $ 58.290,10 US dollars, the state of income in the first year is $ 3.040,36 US dollars and cash flow is $ 52,74 US dollars. The financial evaluation the following results were determined: Net (VAN), Present Value is $ 31.273,95 Internal Rate of Return (IRR) is 45,85% Benefit Cost Ratio (RB / C) it is $ 1,15 The Recovery Period Capital (PR / C) is achieved at 1 year, 4 months and 24 days. In the sensitivity analysis, it is reiterated that the project is not sensible, because it supports changes in the market either by increasing the costs of a 15,16% and a decrease in revenue of 12,41%. The conclusions are the most important synthesis of the results of the research; It also raises the respective necessary recommendations for further implementation.